Measurement and Analysis of Differences in The Impact of The Implementation of Large-Scale Social Restrictions (PSBB) Based on The Mann Whitney Test - Bambang Budiarto (Universitas Muhammadiyah Sidoarjo, 2021)
This research is a non-parametric statistical measurement form which use the Mann Whitney Test. The aim is to determine whether or not there are differences in the impact of the implementation of the PSBB as a result of Covid-19 pandemic in the Surabaya, Gresik and Sidoarjo areas through the distribution of questionnaires and interviews, a sample of 134 people who were distributed in the 3 regions obtained. From the results of repeated simulations, measurements and testing to answer existing hypotheses, it can be seen that there are 3 things that are the conclusions of this study. The first conclusion, that there is no difference in the impact of the PSBB implementation in the Sidoarjo and Surabaya areas, which use α = 5%, the value obtained Zcount = -0.65745 is higher than Ztabel = +/- 1.96. It is in the receiving area which means H0 or the hypothesis that there is no difference in the impact of the PSBB implementation between Sidoarjo and Surabaya areas cannot be rejected. The second conclusion, that there are differences in the impact of the PSBB implementation in the Surabaya and Gresik areas with the result that the value of Zcount = -2.28792 is lower than Ztable. The same thing happened in the third test, there was a significant difference in the impact of the PSBB implementation in Sidoarjo and Gresik areas. Furthermore, in the descriptive analysis, there are several factors were found which effect the three tests result, as follows: geographic, demographic, social, cultural and employment factors.